Exploring Potentially Hazardous Areas for Water Quality Using Dynamic Factor Analysis - Kovács, József; Márkus, László; Szalai, József; Barcza, Márton; Bernáth, György; Székely, Ilona Kovácsné; Halupka, Gábor (IntechOpen, 2012)
None